الشعور بالذات وعلاقته بالأفكار اللاعقلانية لدى عينة من طلبة الصف الأول الثانوي بمدينة دمشق - عاقل, جبران (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This study aims to identify the relationship between self- Consciousness and the irrational thoughts and how this relationship may vary on the basis of sexual differentiation. The sample of the study consists of (330) students from the first secondary class (150 male, 180 female). The study has used the self- Consciousness scale (Fenigstein, et.al., 1975) and the irrational thoughts scale (Al-mougharbel, 2010). The findings indicate that there is a statistically significant relationship between the private and the public self-consciousness along with the irrational thoughts. In addition, there are differences in self- Consciousness resulting from sexual differentiation and are in favor of females. There are also no differences in the irrational thoughts depending on the basis of sexual differentiation.هدف البحث الحالي إلى دراسة العلاقة بين الشعور بالذات والأفكار اللاعقلانية، كما هدف إلى تعرف الفروق في الشعور بالذات والأفكار اللاعقلانية تبعاً لمتغير الجنس. تكونت عينة البحث من(330)طالباً وطالبة من طلبة الصف العاشر الثانوي بمدينة دمشق. واستخدم في البحث مقياس الشعور بالذات (اعداد فينيشتاين وآخرون 1975) ومقياس الأفكار اللاعقلانية (اعداد المغربل 2010). توصل البحث إلى أنه توجد علاقة دالة احصائياً بين الشعور الخاص والعام بالذات والأفكار اللاعقلانية لدى عينة البحث. كما توجد فروق في الشعور بالذات تبعاً لمتغير الجنس ولصالح الاناث. لا توجد فروق في الأفكار اللاعقلانية تبعاً لمتغير الجنس.